The effect of vent size and congestion in large-scale vented natural gas/air explosions. (May 2015) - Tomlin, G.; Johnson, D.M.; Cronin, P.; Phylaktou, H.N.; Andrews, G.E.
Abstract: A typical building consists of a number of rooms; often with windows of different size and failure pressure and obstructions in the form of furniture and décor, separated by partition walls with interconnecting doorways. Consequently, the maximum pressure developed in a gas explosion would be dependent upon the individual characteristics of the building. In this research, a large-scale experimental programme has been undertaken at the DNV GL Spadeadam Test Site to determine the effects of vent size and congestion on vented gas explosions. Thirty-eight stoichiometric natural gas/air explosions were carried out in a 182 m 3 explosion chamber of L/D = 2 and KA = 1, 2, 4 and 9. Congestion was varied by placing a number of 180 mm diameter polyethylene pipes within the explosion chamber, providing a volume congestion between 0 and 5% and cross-sectional area blockages ranging between 0 and 40%. The series of tests produced peak explosion overpressures of between 70 mbar and 3.7 bar with corresponding maximum flame speeds in the range 35–395 m/s at a distance of 7 m from the ignition point. The experiments demonstrated that it is possible to generate overpressures greater than 200 mbar with volume blockages of as little as 0.57%, if there is not sufficient outflow through the inadvertent venting process. The size and failure pressure of potential vent openings, and the degree of congestion within a building, are key factors in whether or not a building will sustain structural damage following a gas explosion. Given that the average volume blockage in a room in a UK inhabited building is in the order of 17%, it is clear that without the use of large windows of low failure pressure, buildings will continue to be susceptible to significant structural damage during an accidental gas explosion. Highlights: Large-scale tests have been carried out to consider the development of vented gas explosions. The series of tests produced peak explosion overpressures of between 70 mbar and 3.7 bar. Overpressures greater than 200 mbar were generated with volume blockages of as little as 0.57%.